2019
DOI: 10.1042/bsr20182375
|View full text |Cite|
|
Sign up to set email alerts
|

Responses of apoptosis and matrix metabolism of annulus fibrosus cells to different magnitudes of mechanical tension in vitro

Abstract: Background: Annulus fibrosus (AF) is important to confine disc nucleus pulposus (NP) tissue during mechanical load experience. However, the knowledge on AF cell biology under mechanical load is much limited compared with disc NP. Objective: The present study aimed to investigate responses of apoptosis and matrix metabolism of AF cells to different magnitudes of mechanical tension in vitro. Methods: Rat AF cells were subjected to different magnitudes (5, 10, and 20% elongations at a frequency of 1.0 Hz for 6 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Cells of the AF tissue originate from mesenchyme and present many features similar to fibroblasts and chondrocytes [10,11]. AF cells help to maintain the structural integrity through synthesizing and secreting normal and adequate extracellular matrix, whereas some intrinsic and extrinsic pathways activated by the detrimental pathological factors often induce AF cell apoptosis [12,13]. In the previous animal disc degeneration models [12,14], the number of apoptotic AF cells is significantly increased, indicating that AF cell apoptosis is promoted and involved in the progression of disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Cells of the AF tissue originate from mesenchyme and present many features similar to fibroblasts and chondrocytes [10,11]. AF cells help to maintain the structural integrity through synthesizing and secreting normal and adequate extracellular matrix, whereas some intrinsic and extrinsic pathways activated by the detrimental pathological factors often induce AF cell apoptosis [12,13]. In the previous animal disc degeneration models [12,14], the number of apoptotic AF cells is significantly increased, indicating that AF cell apoptosis is promoted and involved in the progression of disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Ao et al 16 are in agreement with us in that they found in a bipedal standing-induced IDD model that MP significantly activated the HIF-1α/NF-κB signaling pathway, leading to restricted proliferation of NPCs and extracellular matrix (mainly COL2A1) degradation increase, which in turn leads to IDD. Jiang et al 17 made similar findings by treating fibrocystic ring cells with different deformation rates of draw mechanical stress. Their results showed that a deformation rate of 5% was not sufficient to affect the phenotype of fibrous ring cells, but when the deformation rate was increased from 10% to 20%, the phenotype of the cells was significantly altered with the increase in deformation rate.…”
Section: Discussionmentioning
confidence: 68%
“…A human AF tissue level analysis exhibited that the tensile hoop stress can reach 12.7 MPa [13]. Several studies have verified the apoptosis of AFCs significantly rises with the elevation of aberrant mechanical loading degree [7,[14][15][16]. Therapies that inhibit aberrant mechanical loading-induced AFCs apoptosis can result in alleviated IVDD in animal experiments [17,18].…”
Section: Introductionmentioning
confidence: 99%